Cerebral grey matter density is associated with neuroreceptor and neurotransporter availability: A combined PET and MRI study - Manninen Sandra; Karjalainen Tomi; Tuominen Lauri J; Hietala Jarmo; Kaasinen Valtteri; Joutsa Juho; Rinne Juha; Nummenmaa Lauri (Elsevier BV, 2022)
Positron emission tomography (PET) can be used for in vivo measurement of specific neuroreceptors and transporters using radioligands, while voxel-based morphometric analysis of magnetic resonance images allows automated estimation of local grey matter densities. However, it is not known how regional neuroreceptor or transporter densities are reflected in grey matter densities. Here, we analyzed brain scans retrospectively from 328 subjects and compared grey matter density estimates with neuroreceptor and transporter availabilities. µ-opioid receptors (MORs) were measured with [11C]carfentanil (162 scans), dopamine D2 receptors with [11C]raclopride (92 scans) and serotonin transporters (SERT) with [11C]MADAM (74 scans). The PET data were modelled with simplified reference tissue model. Voxel-wise correlations between binding potential and grey matter density images were computed. Regional binding of all the used radiotracers was associated with grey matter density in region and ligand-specific manner independently of subjects’ age or sex. These data show that grey matter density and MOR and D2R neuroreceptor / SERT availability are correlated, with effect sizes (r2) ranging from 0.04 to 0.69. This suggests that future studies comparing PET outcome measure different groups (such as patients and controls) should also analyze interactive effects of grey matter density and PET outcome measures.